Wheeled Mobile Robot Path Control in a Complex Trajectory using HybridMethods - Ali, Mohammed A. H.; Musa, Mailah; Wan Azhar, Wan Yusoff; Zamzuri, Hamedon; Zulkifli, Md. Yusof (WSEAS Press, 2015)
A robust control algorithm for tracking the mobile robot in a pre-planned path during passing through complicated environments such as in roundabout is presented in this paper. The proposed algorithm is derived from the kinematic and dynamic of 3wheeled Non-holonomic mobile robot motion. The control scheme is performed using Resolved Acceleration Control, Active Force Control strategy or mixed of them in Simulink-MATLAB, which are compared with each other in the matter ofenabling the robot to follow the predefined path while applying disturbances. Results show the capability of this controller to track the robot on the pre-defined path and remove the effect of the disturbances.